Photoelectrochemically deposited Sb2Se3 thin films: deposition mechanism and characterization1. Issue 104 (11th November 2015) - Yang, Jia; Lai, Yanqing; Fan, Yanyun; Jiang, Yan; Tang, Ding; Jiang, Liangxing; Liu, Fangyang; Li, Jie
<x xml:space="preserve">Abstract</x> Photoelectrochemically deposited (PED) Sb2Se3 thin films present interesting properties and performance. PED can enhance the electroreduction process, which will result in the settlement of the dilemma of compound semiconductor electrodeposition.